Open is not enough - Chen, Xiaoli; Neubert, Sebastian (Nature physics, 2019)
The solutions adopted by the high-energy physics community to foster reproducible research are examples of best practices that could be embraced more widely. This first experience suggests that reproducibility requires going beyond openness.